Sepsis Triggers a Late Expansion of Functionally Impaired Tissue-Vascular Inflammatory Monocytes During Clinical Recovery - Baudesson de Chanville, Camille; Chousterman, Benjamin Glenn; Hamon, Pauline; Laviron, Marie; Guillou, Noelline; Loyher, Pierre Louis; Meghraoui-Kheddar, Aida; Barthelemy, Sandrine; Deterre, Philippe; Boissonnas, Alexandre; Combadière, Christophe (Frontiers in Immunology, 2020)
Sepsis is characterized by a systemic inflammation that can cause an immune dysfunction, for which the underlying mechanisms are unclear. We investigated the impact of cecal ligature and puncture (CLP)-mediated polymicrobial sepsis on monocyte (Mo) mobilization and functions. Our results show that CLP led to two consecutive phases of Mo deployment. The first one occurred within the first 3 days after the induction of the peritonitis, while the second phase was of a larger amplitude and extended up to a month after apparent clinical recovery. The latter was associated with the expansion of Mo in the tissue reservoirs (bone marrow and spleen), their release in the blood and their accumulation in the vasculature of peripheral non-lymphoid tissues. It occurred even after antibiotic treatment but relied on inflammatory-dependent pathways and inversely correlated with increased susceptibility and severity to a secondary infection. The intravascular lung Mo displayed limited activation capacity, impaired phagocytic functions and failed to transfer efficient protection against a secondary infection into monocytopenic CCR2-deficient mice. In conclusion, our work unveiled key dysfunctions of intravascular inflammatory Mo during the recovery phase of sepsis and provided new insights to improve patient protection against secondary infections.